VD_FINDINFO Décision / 2013 / 970 vom 25. November 2013 - VD Tribunal cantonal (2013)
RISQUE DE RÉCIDIVE, DÉTENTION PRÉVENTIVE, RÉGIME DE LA DÉTENTION | 221 al. 1 let. c CPP (CH), 393 al. 1 let. c CPP (CH)